Understanding and Addressing Poverty in Malang City: AQualitative Content Analysis of Socioeconomic Factors andPolicy Implications - Kawakibi, Ardhan Ardiansyah; Solikah (PANGRIPTA, 2024)
The phenomenon raised in this research is that poverty is a serious challenge in Malang City, although the level is decreasing. The government focuses on updating welfare data and strengthening education. Factors such as low minimum wages and school dropout rates influence poverty. The study of these factors is important for effective poverty reduction policies in Malang City. This research aims to understand and overcome poverty in Malang City effectively and sustainably. The research method used is qualitative content analysis study by collecting data in the form of content analysis, documentation, and interviews and electronic newspapers in Malang City with the aim of obtaining written or printed information in the mass media. The results obtained from this research activity show that although the percentage of poverty is stable, the absolute number of poor people in Malang City continues to increase from year to year. The upward trend in the poverty line is not always consistent with the percentage of poor people, which highlights the complexity of the social and economic challenges faced by the people of Malang City.